An Evaluation of CXCR4 Targeting with PAMAM Dendrimer Conjugates for Oncologic Applications - Wojciech G. Lesniak; Babak Behnam Azad; Samit Chatterjee; Ala Lisok; Martin G. Pomper (Pharmaceutics, 2022)
The chemokine receptor 4 (CXCR4) is a promising diagnostic and therapeutic target for the management of various cancers. CXCR4 has been utilized in immunotherapy, targeted drug delivery, and endoradiotherapy. Poly(amidoamine) [PAMAM] dendrimers are well-defined polymers with unique properties that have been used in the fabrication of nanomaterials for several biomedical applications. Here, we describe the formulation and pharmacokinetics of generation-5 CXCR4-targeted PAMAM (G5-X4) dendrimers. G5-X4 demonstrated an IC50 of 0.95 nM to CXCR4 against CXCL12-Red in CHO-SNAP-CXCR4 cells. Single-photon computed tomography/computed tomography imaging and biodistribution studies of 111In-labeled G5-X4 showed enhanced uptake in subcutaneous U87 glioblastoma tumors stably expressing CXCR4 with 8.2 ± 2.1, 8.4 ± 0.5, 11.5 ± 0.9, 10.4 ± 2.6, and 8.8 ± 0.5% injected dose per gram of tissue at 1, 3, 24, 48, and 120 h after injection, respectively. Specific accumulation of [111In]G5-X4 in CXCR4-positive tumors was inhibited by the peptidomimetic CXCR4 inhibitor, POL3026. Our results demonstrate that while CXCR4 targeting is beneficial for tumor accumulation at early time points, differences in tumor uptake are diminished over time as passive accumulation takes place. This study further confirms the applicability of PAMAM dendrimers for imaging and therapeutic applications. It also emphasizes careful consideration of image acquisition and/or treatment times when designing dendritic nanoplatforms for tumor targeting.